2008
DOI: 10.1192/bjp.bp.106.025981
|View full text |Cite|
|
Sign up to set email alerts
|

Computerised cognitive-behavioural therapy for depression: systematic review

Abstract: There is some evidence to support the effectiveness of CCBT for the treatment of depression. However, all studies were associated with considerable drop-out rates and little evidence was presented regarding participants' preferences and the acceptability of the therapy. More research is needed to determine the place of CCBT in the potential range of treatment options offered to individuals with depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
152
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(160 citation statements)
references
References 14 publications
5
152
0
3
Order By: Relevance
“…86 Other reviews showed that telemedicine, 78 internet-based interventions and support 82 and computerised CBT 81 improved symptoms. Positive effects were found in three of the four RCTs of computerised CBT for mild to moderate depression 85 and improvements in mental health were linked to the MoodGYM and BluePages programmes in particular. 84 Three of the five systematic reviews with meta-analyses considering mental health problems or anxiety disorders reported moderate to large effects for mental health and/or anxiety.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…86 Other reviews showed that telemedicine, 78 internet-based interventions and support 82 and computerised CBT 81 improved symptoms. Positive effects were found in three of the four RCTs of computerised CBT for mild to moderate depression 85 and improvements in mental health were linked to the MoodGYM and BluePages programmes in particular. 84 Three of the five systematic reviews with meta-analyses considering mental health problems or anxiety disorders reported moderate to large effects for mental health and/or anxiety.…”
Section: Resultsmentioning
confidence: 99%
“…There was evidence of improved patient outcomes, including quality of life and medication adherence, for telehealth interventions for depression, [78][79][80]85,94 anxiety-related disorders 87,89 and post-traumatic stress disorder (PTSD). 88,95 Systematic reviews with meta-analyses for depression reported positive effects for telephone-based psychotherapy for depression, 79 internet-based CBT 80 and computerised psychological treatment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-acceptability -refusal to begin treatment -is a noted problem in the literature on cCBT 81 and it is likely to be especially relevant in routine primary care, where not all individuals are likely to be willing to try cCBT. 82 We therefore revised our original protocol to allow us to explore reasons for treatment refusal in an attempt to understand perceived barriers to using cCBT and to identify how treatment uptake can be improved. We thus amended the original protocol.…”
Section: Qualitative Studymentioning
confidence: 99%
“…But, they also highlights that the dropout rate in MoodGYM studies could be a problem [17]. Another systematic review of the computerized CBT delivery methods conducted by Kaltenthaler et al also highlights that the dropout rates for the different computerized CBT delivery methods are quite high [18]. The high dropout rates for the computerized CBT delivery could be due to usability and accessibility.…”
Section: Methodsmentioning
confidence: 99%